A contribuição da facilitação gráfica na gestão colaborativa de projetos de inovação em instituições de ensino superior - Ribeiro, Maxiliano (2020)
This Doctoral Thesis discusses the contributions of graphic facilitation to the collaborative management of innovation projects in Higher Education Institutions. This work is justified by carrying out studies aimed at innovation projects and collaborative project management, and proposes a methodology for collaborative management of innovation projects through graphic facilitation. The research methodology was initially outlined in three complementary analytical categories: graphic facilitation, collaborative project management and innovation projects. The level of analysis is Higher Education Institutes (HEIs) with innovative projects, so this study was carried out at the Federal University of Paraná (UFPR). The units of analysis are two innovation projects, as follows: Open education model for Engineer and Architect - dissemination of research on sustainability; and Dissemination of knowledge through transversal and hybrid disciplines in the form of Massive Open and Online Courses. The type of research is characterized as exploratory; the technique of data collection as action research; the temporal cut is transversal, being the instruments of collection of bibliographic, documental data, participant observation and interview. The approach is qualitative and the method of analysis would be content analysis, document analysis and graphic facilitation. The main contributions of graphic facilitation to the collaborative management of innovation projects in HEIs are the adoption of new models of collaborative management of innovation projects with the application of visual language; understanding of the different innovations that require different approaches to project management; expansion of the capacity to share information; increase in the occurrence of scientific research on the topic of graphic facilitation; use of visual methods in conducting groups; favoring the connection between people and innovation projects; understanding of the general concept of the innovation project, through visual means; minimizing uncertainties in innovation projects using graphical facilitation; visual adaptation of collaborative management strategies for innovation projects; promoting the union of different forms of project management; creation of figurative scenarios; adopting an alternative look at the collaborative management of innovation projects; conducting groups of visual projects; creation of graphic records of innovation projects; facilitation in visual meetings of project teams; creation of graphic processes in innovation projects; adhesion of visual information design to projects; and generating a personal link with the project through visual means.